pre-writing stage The most important of them for the beginner and how to train them (Journal of the College of Basic Education, 2022)
If reading is one of the windows of knowledge; It is one of the most important educational toolsMan stands on the results of human thought; Writing is - in fact - a pridethe human mind; Rather, it is the greatest thing that the mind has produced. (Fadlallah 2008: 53) and (Madkoor9 265) and (Al-Khafs 0 2014: 196).Writing is the greatest discovery made by man during his long history ©He was able to record his production and heritage. And to take from the past and present what preparesway for subsequent generations. (Al-Jaafrah. 2011: 273).Writing is the memory of the individual and the nation. It is a record of all aspects of his life and is a source of nooverflowing with all knowledge and sciences; And our whole life is linked directly or indirectly